Gender-Specific Aspects of Teachers Regarding Working Behavior and Early Retirement - Kreuzfeld, Steffi; Seibt, Reingard (Frontiers in Psychology, 2022)
Worldwide, a significant proportion of teachers retire prematurely for health reasons or at their own request. The study examines whether male and female teachers differ in terms of working conditions and coping with high work demands as well as individual factors that promote early retirement. A cross-sectional study was conducted to collect data from 6,109 full-time teachers in high schools (56 % women). Weekly working hours from a four-week working time record and psychosocial work stress (effort-reward model, ER ratio) were used as workloads. In addition, emotional exhaustion (Maslach Burnout Inventory) and coping strategies that endangered health were recorded in the form of overcommitment and inability to recover. Also, the teachers gave a prediction and reasons for early retirement and made their own suggestions on how to prevent this. The results show that both workloads and emotional exhaustion are comparable between the genders, but women have a greater tendency than men to overcommit and be unable to recover. As ER ratio and emotional exhaustion increase, the chances for both genders to reach the regular retirement age decrease significantly; for health-endangering coping strategies, the relationship is somewhat weaker. The majority of male and female teachers (79 %) indicate excessive workloads as the main reason for leaving the profession early. In order to protect teachers from high workloads, measures at the organizational, social and individual level are necessary. Proposals for schools and policy makers are critically discussed on the basis of teacher recommendations.